Modularity of arithmetic special divisors for unitary Shimura varieties (with an appendix by Yujie Xu) - Congling Qiu; Yujie Xu (Forum of Mathematics, Sigma)
We construct explicit generating series of arithmetic extensions of Kudla’s special divisors on integral models of unitary Shimura varieties over CM fields with arbitrary split levels and prove that they are modular forms valued in the arithmetic Chow groups. This provides a partial solution to Kudla’s modularity problem. The main ingredient in our construction is S. Zhang’s theory of admissible arithmetic divisors. The main ingredient in the proof is an arithmetic mixed Siegel-Weil formula.